Thermodynamic study of the interactions of salicylic acid and granular activated carbon in solution at different pHs - Valentina Bernal; Liliana Giraldo; Juan C Moreno-Piraján (Adsorption Science & Technology)
The inappropriate use of pain medication has led to the appearance of salicylic acid molecules (aspirin’s metabolite excretion) in surface water, which causes problems for the environment. The adsorption process using activated carbon is one of the processes that is used for the removal of organic compounds present in the aqueous phase; however, the percentage of removal depends on the physicochemical properties of the adsorbent and the adsorbate such as: pore size, surface area, surface chemistry, molecular size and solubility. In this work, we have studied the adsorbent–adsorbate interactions through the determination of the immersion enthalpy of the activated carbon in salicylic acid aqueous solutions; due to the solute and activated carbon surface have functional groups capable of ionized with the pH, the adsorption study was carried out at pH 2, 7, and 11. The activated carbons selected for the study were a granular activated carbon and a reduced activated carbon to 1173 K; as the immersion liquid were used salicylic acid aqueous solutions with concentrations between 0.072 mmol/ l and 0.72 mmol/ l, the solutions at pH 2 and 11 were prepared with HCl and NaOH solutions, respectively. It was determined that the immersion enthalpy is between −7.39 J /g and −22.5 J/g for the reduced activated carbon and between −7.63 J/g and −16.73 J/g for the granular activated carbon.